Golden Generation: Efforts to Counseling Drug-Free Parenting in the Family Environment for Family Empowerment and Welfare Members - Hardiansyah Hardiansyah; Edi Saputro; Rayhan Norviandy; Yoga Putra Fathar; Amar Ma’ruf; Muhammad Raditya Aditya; Firjatullah Firjatullah (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2024)
Drug abuse has become a serious issue in Sindang Sari Village, Samarinda, due to the lack of understanding about the dangers of drugs. The aim of this community service by the researchers is to enhance the knowledge of the KB Village (Quality Family) cadres on drug prevention and the crucial role of parents in shaping resilient children. The counseling method was carried out by students of Psychology and Social and Political Sciences to 13 members of the PKK, and the evaluation was conducted through pre-tests and post-tests. The results showed a significant increase in the knowledge of the KB Village cadres after the counseling (mean pre-test: 4.83, mean post-test: 6.92). It was concluded that there was an increase in understanding and knowledge regarding drug-free parenting among PKK members.. This research highlights the family as a primary stronghold in preventing drug abuse. Proper parenting practices can help children avoid misuse of substance. Therefore, it is crucial to strengthen the role of families in drug prevention efforts.Penyalahgunaan narkoba menjadi permasalahan serius di Kelurahan Sindang Sari, Samarinda, dengan minimnya pemahaman tentang bahayanya narkoba. Tujuan pengabdian dari peneliti untuk meningkatkan pengetahuan anggota kampung KB (keluarga Berkualitas) tentang pencegahan narkoba dan peran penting orang tua dalam membentuk anak yang tangguh. Metode Penyuluhan dilakukan oleh mahasiswa Psikologi Ilmu Sosial dan Ilmu Politik kepada 13 anggota PKK dan evaluasi dilakukan melalui pre-test dan post-test. Hasil terjadi peningkatan signifikan dalam pengetahuan anggota kampung KB setelah penyuluhan (mean pre-test: 4.83, mean post-test: 6.92). Disimpulkan bahwa meningkatnya pemahaman dan pengetahuan mengenai pola asuh yang bebas narkoba pada anggota PKK. Implikasi dalam penelitian ini adalah Penelitian ini menunjukkan bahwa keluarga merupakan benteng utama dalam pencegahan narkoba. Pola asuh yang tepat dari orang tua dapat membantu anak-anak terhindar dari penyalahgunaan narkoba. Oleh karena itu, penting untuk meningkatkan peran keluarga dalam upaya pencegahan narkoba.